Early gastric cancer: 46 cases treated in one surgical department. Issue 10 (October 1992) - Sue-Ling, H M; Martin, I; Griffith, J; Ward, D C; Quirke, P; Dixon, M F; Axon, A T; McMahon, M J; Johnston, D
Abstract : Forty six consecutive patients with early gastric cancer were treated between 1970 and 1990. The proportion of cases of early gastric cancer increased significantly (p < 0.01) from 1% of all cases in the first five year period to 15% in the last five year period, because of greater awareness of the condition and more widespread use of endoscopy. There were 33 men and 13 women, of median age 69 years (range 38-86). Most patients (91%) presented with symptoms indistinguishable from those of peptic ulceration. The median duration of symptoms was four months (range 0.1-36 months). All 46 patients were treated surgically. Three patients (6.5%) died after operation and a further 10 (22%) suffered postoperative complications. None of the surviving patients has been lost to follow up and 25 have been followed up for a minimum period of five years. Five year survival by life table analysis was 98%. These findings suggest that in Britain in the 1990s, as in Japan, it may be possible to diagnose an increasing proportion of patients with gastric cancer at a relatively early pathological stage, when most patients can be cured by radical surgical resection with lymphadenectomy.